MULTIMEDIA APPLICATIONS FOR KNOWN THE HISTORY OF ISLAMIC CULTURE IN supportive learning Madrasah Tsanawiyah using Macromedia FLASH 8 - KHAIRUL IKHWAN (Jurnal Sistem Informasi, 2007)
Surrounding historical knowledge: knowledge of the events the past and the knowledgeof how to think historically. History of Islamic culture began in the Umayyad dynastyuntil the Abbasid dynasty. These multimedia applications are made with a fairlyinteresting presentation using Macromedia Flash 8 which is known as an animationmaker application programs and also to use other software like Audio Recorder for Freeto add a human voice, so the user simply by listening to the content of the materialpresented.